Investigating the Role of LED as a Tool for Poverty Alleviation in Mbombela Municipality - Mahlalela, Simangele (My University, 2014)
Since 1994, with the dawn of democracy, South Africa has remained with the challenge of reintegrating itself into the global economy and addressing the imbalances created by the apartheid regime. There have been a plethora of policies underpinned by neo-marxist and neo-liberal ideals that have been adopted by the state in order to promote economic growth and poverty alleviation. Amongst these policies are the Local Economic Development (LED) policies which have been aimed at growing local economies as well as to uplift previously disadvantaged groups. South Africa has been experiencing difficulties in finding a balance between developing pro-growth and pro-poor LED strategies and this has led to the criticism that ‘LED strategies in the country tend to be pro-growth rather than pro-poor’ . Due to this argument, the role of LED as a tool for poverty alleviation has therefore been challenged and this research report stems from that concern. The purpose of this research report is explore the concept of pro-poor LED in South Africa and to investigate how it is able to contribute towards poverty alleviation at a local context. The study area, Mbombela Municipality, forms the basis for this investigation in the exploration of four aspects of LED, namely; provision of services, infrastructure development (roads), job creation and business creation. The finding is that LED in Mbombela has not yet been able to impact on poverty alleviation significantly and this is due to the municipality’s lack of effective pro-poor strategies, poor implementation of projects and lack of resources and capacity.
Planning Honours Report 2014, Wits University
Keywords: local economic development, poverty alleviation; local economic development, poverty alleviation